Cloning, Overexpression, and Characterization of a Thermostable Nitrilase from an Antarctic Pyrococcus Sp. - Blamey-Alegria, J (Springer Tokyo, 2017)
Nitriles are important chemical building blocks for the synthesis of intermediates in fine chemical and pharmaceutical industries. Here, we report a new highly thermostable nitrilase from an Antarctic Pyrococcus sp. MC-FB, a hyperthermophilic archaeon. A gene that encoded a nitrilase was identified and subsequently cloned and overexpressed in Escherichia coli. The recombinant nitrilase, named NitMC-FB, is active as a homodimer (60 kDa) with an optimal temperature and pH of 90 °C and 7.0, respectively. NitMC-FB hydrolyzes preferentially aromatic nitriles, being the first aromatic nitrilase from an archaeon described so far. The KM and Vmax parameters were determined to be 13.9 mM and 3.7 μmol/min*mg, respectively, with 2-cyanopyridine as the substrate. Additionally, the recombinant nitrilase is highly thermostable with a half-life of 8 h at 90 °C. © 2017, Springer Japan KK.